A design method for metamaterials: 3D transversely isotropic lattice structures with tunable auxeticity. (21st December 2021) - Peng, Xiang-Long; Bargmann, Swantje
Abstract: A method for designing 3D transversely isotropic auxetic lattice structures is proposed. Based on it, two new auxetic structures have been designed. Systematically, their effective elastic properties are investigated computationally and analytically in all loading directions. The effective Young's moduli and Poisson's ratios within the transverse plane and those along the longitudinal direction are widely tunable by tailoring the structural geometry. Both structures exhibit transverse and longitudinal auxeticities concurrently as well as separately. The proposed auxetic structures expand the existing auxetic material space in terms of elastic anisotropy.